Harmonization of Mining Laws Post-Centralization in the Implementation of the Regional Action Plan for Mercury Reduction and Elimination (RAD-PPM) in West Kalimantan Province - Herbin Mardongan Sihombing; Laksanto Utomo; Amalia Syauket (Asian Journal of Social and Humanities, 2026)
This research is motivated by the centralization of mining affairs from regional to central government under Law No. 3 of 2020 on Mineral and Coal Mining, creating a legal gap in West Kalimantan Province. The region remains burdened with obligations to implement the RAD-PPM under the Minamata Convention Ratification (Law No. 11 of 2017) to mitigate impacts of Artisanal and Small-scale Gold Mining (PESK/PETI), while licensing control and operational supervision have been entirely withdrawn to the Central Government. This study analyzes the juridical harmonization of this gap and formulates strengthened Forkopimda governance to address obstacles in ecological supervision of community mining. The method used is normative-empirical legal research with a qualitative approach, employing Statutory Approach, Content Analysis, and Sociological Jurisprudence through interviews with the West Kalimantan DLHK, Mining Inspectors, and civil society organizations, analyzed using the Theory of Authority and Soerjono Soekanto's Theory of Legal Effectiveness. Results show that centralization triggers a norm antinomy and regulatory vacuum in operationalizing RAD-PPM, necessitating vertical delegation of remaining authorities. Overcoming multidimensional barriers limited infrastructure, budgets, and miners' dependence on mercury requires strengthening Forkopimda as an integrative harmonizer, ensuring law enforcement is not merely repressive but also accommodative toward legalizing People's Mining Areas (WPR) and non-mercury technology substitution for sustainable ecological justice.